PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL PYTHAGORAS PADA MATA PELAJARAN MATEMATIKA DI KELAS VIII.1 SMP NEGERI 4 BASO - Usyeldi Usyeldi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Mathematics instructional in Junior High School (SMPN) 4 Baso, Agam conducted through lecture method. The student-centered learning has not been performed at instructional. Most of students (60%) have not been mastered of mathematics. One of the efforts to improve learning outcomes is to use the Pythagorean model as a learning media. This research aims to improve the learning outcomes of students used the Pythagorean model of the Pythagorean Theorem. The research used classroom action research design. The research subjects were VIII.1 grade students of SMPN 4 Baso, Agam in the 2015/2016 academic year of 20 students. Data collection instrument were tests and observation sheet. The test was used to know the learning outcomes of students in each cycle. Observation sheet was used to determine the instructional process at each cycle. Data were analyzed with descriptive statistics. The results showed that: The average score of the students learning outcome in the first cycle of 66.5, the second cycle of 75.5 so that was increasing in the average score of the first cycle to the second cycle. Percentage of mastery learning of students in the first cycle of 60%, in the second cycle of 95%. Thus there was an improved of mastery learning of students from the first cycle to the second cycle. It can be concluded that the mathematics instructional by using Pythagoras models can improve to learning outcomes of students.